Peran Komunikasi Keluarga dalam Membangun Resiliensi Remaja Madya Fatherless di Jakarta Barat - Afriliani, Aulia; Rahman, Nurlina; Praptiningsih, Novi Andayani (Communicology: Jurnal Ilmu Komunikasi, 2025)
This article aims to explain how family communication resilience is formed in middle adolescents experiencing fatherless conditions. The problem is focused on the patterns of family communication that contribute to building adolescents' psychological resilience and the role of father-substitute figures within the family. To approach this issue, the study refers to the theoretical framework of family resilience by Froma Walsh and interpersonal communication theory. Data were collected through a qualitative method using a phenomenological approach, involving in-depth interviews with five middle adolescents living in West Jakarta who have experienced fatherlessness. The data were analyzed thematically based on the participants' subjective experiences. This study concludes that open communication, emotional support from mothers or substitute figures, and involvement in positive activities are key factors in developing adolescent resilience. In addition, adolescents show the ability to manage emotions and construct positive meaning from their life situations. These findings emphasize the importance of strengthening family roles and social environments in supporting adolescents to cope with the absence of a father figure.   Keywords: Adolescent Resilience; Emotional Support; Fatherless: Family Communication; Phenomenology   ABSTRAK Penelitian ini bertujuan untuk menjelaskan bagaimana resiliensi komunikasi keluarga terbentuk pada remaja madya yang mengalami kondisi fatherless. Masalah difokuskan pada bentuk komunikasi keluarga yang berperan dalam membentuk ketahanan psikologis remaja serta dukungan dari figur pengganti ayah dalam keluarga. Guna mendekati masalah ini dipergunakan acuan teori dari resiliensi keluarga Froma Walsh dan teori komunikasi interpersonal. Data-data dikumpulkan melalui metode kualitatif dengan pendekatan fenomenologi, menggunakan wawancara mendalam terhadap lima remaja madya yang tinggal di Jakarta Barat dan mengalami kondisi fatherless. Data dianalisis secara tematik berdasarkan pengalaman subjektif para informan. Kajian ini menyimpulkan bahwa komunikasi terbuka, dukungan emosional dari ibu atau figur pengganti, serta keterlibatan dalam kegiatan positif merupakan faktor utama yang membentuk resiliensi remaja. Selain itu, remaja juga menunjukkan kemampuan mengelola emosi dan membangun makna positif terhadap situasi yang mereka alami. Temuan ini menggarisbawahi pentingnya penguatan peran keluarga dan lingkungan sosial dalam mendampingi remaja menghadapi kondisi kehilangan figur ayah.   Kata Kunci: Dukungan Emosional; Fatherless; Fenomenologi; Komunikasi Keluarga; Resiliensi Remaja